Programming competencies in university students through game development - Castillo-Salvatierra, Luis; Cárdenas-Cobo, Jesennia; de la Fuente-Burdiles, Claudia; Vidal-Silva, Cristian (Frontiers in Education, 2025)
IntroductionThe growing importance of programming in higher education requires innovative approaches to facilitate learning. Video games have emerged as an engaging tool that enhances problem-solving skills and logical thinking.MethodologyThis study examines the effectiveness of Unity Visual Scripting in fostering programming competencies among university students. A project-based methodology was employed in the course “Physics for Videogames” during the third semester of the Engineering in Video Game Development and Virtual Reality program at the Universidad de Talca, Chile.ResultsThrough game development, students overcame challenges associated with text-based programming. The results indicate significant improvements in students' computational thinking, motivation, and collaboration.DiscussionBy reducing syntactical barriers, Visual Scripting promotes an accessible learning experience that supports the transition to advanced programming concepts. These findings suggest that integrating game development into university curricula enhances digital literacy and fosters an inclusive programming education environment.